2012
DOI: 10.1371/journal.pone.0052014
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension-Linked Mutation of α-Adducin Increases CFTR Surface Expression and Activity in HEK and Cultured Rat Distal Convoluted Tubule Cells

Abstract: The CFTR (Cystic Fibrosis Transmembrane Conductance Regulator) activity and localization are influenced by the cytoskeleton, in particular by actin and its polymerization state. In this study we investigated whether the expression of the hypertensive mutations of α-adducin (G460W-S586C in humans, F316Y in rats), an actin capping protein, led to a functional modification of CFTR activity and surface expression. The experiments were performed on HEK293 T cells cotransfected with CFTR and the human wild type (WT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…2B), as confirmed by calculation of the half time of recovery (t ½ ), after fitting values to one phase decay curves37: t ½ values of LANCL2-PAGFP and of LANCL2-G2A-PAGFP were 50 ± 30 s and 3.4 ± 0.75s, respectively (graph in Fig. 2B; =34 cells from four different transfection experiments, p < 0.001).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…2B), as confirmed by calculation of the half time of recovery (t ½ ), after fitting values to one phase decay curves37: t ½ values of LANCL2-PAGFP and of LANCL2-G2A-PAGFP were 50 ± 30 s and 3.4 ± 0.75s, respectively (graph in Fig. 2B; =34 cells from four different transfection experiments, p < 0.001).…”
Section: Resultssupporting
confidence: 52%
“…Images acquired at the same time points after photoactivation clearly indicated that the fluorescence decay of LANCL2-PAGFP was much slower than that of LANCL2-G2A-PAGFP ( Fig. 2B ), as confirmed by calculation of the half time of recovery (t ½ ), after fitting values to one phase decay curves 37 : t ½ values of LANCL2-PAGFP and of LANCL2-G2A-PAGFP were 50 ± 30 s and 3.4 ± 0.75s, respectively (graph in Fig. 2B ; =34 cells from four different transfection experiments, p < 0.001).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…On the other hand, Mondini et al. () reported that CFTR inh 172 could completely block the whole cell current attributable to transiently transfected CFTR in these HEK‐293 cells. The variability in efficacy of CFTR inh 172 could either be due to differences in the source of the inhibitor, the relative insolubility of the compound in aqueous solution, or in the structure function relationship of the EGFP‐CFTR protein.…”
Section: Discussionmentioning
confidence: 95%
“…However, Mondini et al. () used HEK‐293 cells to examine the effect of a hypertension‐linked mutation of α ‐adducin on CFTR surface expression and channel activity. While in these studies, the HEK‐293 cells were stably transfected with wild type or mutant α ‐adducin, they were transiently transfected with a bicistronic vector, pIRES2‐CFTR‐EGFP, which expressed separate EGFP and CFTR proteins.…”
Section: Discussionmentioning
confidence: 99%